TGFβ1 single-nucleotide polymorphism C-509T alters mucosal cell function in pediatric eosinophilic esophagitis - Duong, L.D.; Rawson, R.; Bezryadina, A.; Manresa, M.C.; Newbury, R.O.; Dohil, R.; Liu, Z.; Barrett, K.; Kurten, R.; Aceves, S.S. (Mucosal immunology, 2020)
Eosinophilic esophagitis (EoE) is a chronic Th2 antigen-driven disorder associated with tissue remodeling. Inflammation and remodeling lead to esophageal rigidity, strictures, and dysphagia. TGFβ1 drives esophageal remodeling including epithelial barrier dysfunction and subepithelial fibrosis. A functional SNP in the TGFβ1 gene that increases its transcription (C-509T) is associated with elevated numbers of esophageal TGFβ1-expressing cells. We utilized esophageal biopsies and fibroblasts from TT-genotype EoE children to understand if TGFβ1 influenced fibroblast and epithelial cell function in vivo. Genotype TT EoE esophageal fibroblasts had higher baseline TGFβ1, collagen1α1, periostin, and MMP2 (p < 0.05) gene expression and distinct contractile properties compared with CC genotype (n = 6 subjects per genotype). In vitro TGFβ1 exposure caused greater induction of target gene expression in genotype CC fibroblasts (p < 0.05). Esophageal biopsies from TT-genotype subjects had significantly less epithelial membrane-bound E-cadherin (p < 0.01) and wider cluster distribution at nanometer resolution. TGFβ1 treatment of stratified primary human esophageal epithelial cells and spheroids disrupted transepithelial resistance (p < 0.001) and E-cadherin localization (p < 0.0001). A TGFβ1-receptor-I inhibitor improved TGFβ1-mediated E-cadherin mislocalization. These data suggest that EoE severity can depend on genotypic differences that increase in vivo exposure to TGFβ1. TGFβ1 inhibition may be a useful therapy in subsets of EoE patients.